Smallholders and urbanization: Strengthening rural-urban linkages to end hunger and malnutrition - da Silva, José Graziano; Fan, Shenggen (International Food Policy Research Institute, 2017)
Rural-urban linkages—including physical, economic, social, and political connections—are crucial for ending hunger and malnutrition (SDG 2) sustainably in both rural and urban areas. Rural-urban linkages also support other Sustainable Development Goals. Urban growth increases food demand and spurs dietary changes in urban areas—new demand can create opportunities for rural producers to improve their livelihoods. Broken value chains and poor coordination weaken rural-urban links and hold back progress on food security and nutrition. Investment in rural infrastructure and intermediate towns—quality rural and feeder roads, electricity, storage facilities, communications and information—can build connections and create hubs of economic activity benefiting smallholders and cities.